From sol to aerogel: a study of the nanostructural characteristics of TEOS derived sonogels - Donatti, D. A.; Ruiz, A. I.; Vollet, D. R. (Elsevier B.V., 2001)
The nanostructural characteristics of acid-catalyzed sonogels are studied along the aging process at 60 degreesC in saturated conditions and after the CO, supercritical extraction (aerogel). The structural evolution was studied by means of small-angle X-ray scattering (SAXS) and UV-Visible absorption techniques. The sonogel exhibits a mass fractal structure in a length scale between zeta - 1/q(0) similar to 5.3 and a(1) similar to 1/q(m) similar to 0.22 nm, as the length scale probed by SAXS. The apparent mass fractal dimension lightly increases from 2.0 for fresh gel until 2.2 for 14 days aging in wet conditions. The UV absorption also increases with the aging time in wet conditions. Both observations are consistent with the syneresis process accompanying the polycondensation progress during aging in saturated conditions. For long aging times, the wet sonogels show a light transition from a mass to a surface fractal. in a very small interval of the length scale, developing an extremely rough surface with fractal dimension D-S similar to 2.9, the fractal characteristics of the sonogels practically do not change with the alcohol exchange. With the CO2 supercritical extraction (aerogel). The interval in the length scale in which the surface fractal is defined increases, while the surface fractal dimension diminishes to D-S similar to 2.5. The mass fractal characteristics are less apparent in the aerogels. (C) 2001 Elsevier B.V. B.V. All rights reserved.